DEVELOPING RETAIL CREDIT AT VIETNAM JOINT STOCK COMMERCIAL BANK FOR INDUSTRY AND TRADE – HA TINH BRANCH - Truong, Thuy Chung (2019)
The research topic of the thesis is through the theoretical foundation of developing retail credit services, analyzing the Bank's current resources in the local operating environment, determining the causes that limit the development of the Bank's retail credit services to show the challenges that banks are facing, Thereby offering solutions to develop retail financial services in the Vietnam Joint Stock Commercial Bank for Industry and Trade - Ha Tinh Branch in the future.